PENGARUH LINGKUNGAN KERJA, PENGAKUAN PROFESIONAL, PELATIHAN PROFESIONAL dan NILAI – NILAI SOSIAL TERHADAP PILIHAN KARIR MAHASISWA SEBAGAI AKUNTAN PUBLIK (Studi Kasus pada Mahasiswa Jurusan Akuntansi di Universitas Islam Malang) - Ayu Octavia Listiana; Nur Diana; Afifudin Afifudin (Universitas Islam Malang, 2020)
ABSTRACTThis study aims to determine the effect of work environment, professional recognition, professional training and social values on student career choices as public accountants (a case study of accounting students at Malang Islamic University). The population in this study were undergraduate students of Accounting Department, Faculty of Economics and Business, Islamic University, class of 2016. The samples in this study were to use purposive sampling technique, namely sampling based on certain criteria. The selected sample is 67 respondents. Data collection was carried out by using a questionnaire method. The data analysis method used is multiple regression analysis. The test data used are simultaneous hypothesis testing (f), determination coefficient (R2), and partial hypothesis testing (t). The results showed that the independent variables simultaneously had a significant effect on the dependent variable. Based on the results of the determination coefficient test, it was found that the Adjusted R value was 62.4%, while 37.6% was the contribution of other variables which were not explained in this study. Based on the partial test results of work environment variables, professional recognition, professional training and social have a positive effect on student career choices as public accountants. Keywords: the effect of work environment, professional recognition, professional training and social values and student career choices as public accountants